2020
DOI: 10.3892/mmr.2020.11712
|View full text |Cite
|
Sign up to set email alerts
|

Platelet isoform of phosphofructokinase promotes aerobic glycolysis and the progression of non‑small cell lung cancer

Abstract: The platelet isoform of phosphofructokinase (PFKP) is a rate-limiting enzyme involved in glycolysis that serves an important role in various types of cancer. The aim of the present study was to explore the specific regulatory relationship between PFKP and non-small cell lung cancer (NSCLC) progression. PFKP expression in NSCLC tissues and corresponding adjacent tissues was detected using reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and immunohistochemical analysis. PFKP expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…It is well documented that HK-II is drastically overexpressed in lung cancer and malignant NSCLC tumor tissues. 49,50 At variance, HK-II is moderately expressed in the adjacent normal tissues. The fact that the expression level of HK-II is significantly higher in the tumor NSCLC tissues, as compared to the normal tissues, designates HK-II as an emerging anticancer therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that HK-II is drastically overexpressed in lung cancer and malignant NSCLC tumor tissues. 49,50 At variance, HK-II is moderately expressed in the adjacent normal tissues. The fact that the expression level of HK-II is significantly higher in the tumor NSCLC tissues, as compared to the normal tissues, designates HK-II as an emerging anticancer therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
“…Aerobic glycolysis provides a material basis for growth and proliferation of tumor cells (28), and large amounts of lactic acid cause invasion of tumor tissues to the normal adjacent tissues (29). In non-small cell lung cancer (NSCLC) cell lines, PFKP was revealed to promote proliferation, migration, invasion, epithelial-mesenchymal transition, and glycolysis (30). Furthermore, PFKP mRNA expression was associated with lymph node metastasis in NSCLC tissues (30).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also have shown that P2RX1 is closely related to the platelet activation pathway [ 27 ]. Phosphofructokinase platelet-type (PFKP) is a rate-limiting enzyme involved in glycolysis and is closely related to the progression of non-small cell lung cancer [ 28 ]. Excised nucleoside triphosphate diphosphate hydrolase (ENTPD) is involved in inflammation and platelet aggregation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%